2018
DOI: 10.1098/rspb.2018.2176
|View full text |Cite|
|
Sign up to set email alerts
|

The rise and fall of dialects in northern elephant seals

Abstract: Vocal dialects are fundamental to our understanding of the transmission of social behaviours between individuals and populations, however few accounts trace this phenomenon among mammals over time. Northern elephant seals (Mirounga angustirostris) provide a rare opportunity to examine the trajectory of dialects in a long-lived mammalian species. Dialects were first documented in the temporal patterns of the stereotyped vocal displays produced by breeding males at four sites in the North Pacific in 1968 and 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The flattening of the hill shape over time as the animal becomes independent of its mother is likely associated with the transition during weaning and less dependency of the calf on the cow. Manatees may undergo periods of crystallization like passerine birds or as speculated for northern elephant seals in which after a certain age the structure of calls and variability of vocal repertoire are fixed 51 , 52 . These age-specific stereotypical hill-shaped features in Florida and Antillean manatees likely evolved to aid cows in discriminating calves from adult conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…The flattening of the hill shape over time as the animal becomes independent of its mother is likely associated with the transition during weaning and less dependency of the calf on the cow. Manatees may undergo periods of crystallization like passerine birds or as speculated for northern elephant seals in which after a certain age the structure of calls and variability of vocal repertoire are fixed 51 , 52 . These age-specific stereotypical hill-shaped features in Florida and Antillean manatees likely evolved to aid cows in discriminating calves from adult conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…The communication range between Northern Elephant Seals depends on the frequency at which they communicate and the properties of the sea water. Studies of Northern Elephant Seals show the emission of sounds at a frequency in the range 150 to 300 Hz (Southall et al, 2003;Casey et al, 2018) and a cochlear sensitivity compatible with this range (Kastak and Schusterman, 1999). Sound absorption in the Pacific Ocean at 100 Hz is of the order of 10 -3 dB km -1 in the Pacific Ocean (Ainslie and McColm, 1998), resulting in a characteristic length for the communication range, obtained as the inverse of the sound absorption, of the order of about one thousand kilometers.…”
Section: Discussionmentioning
confidence: 99%
“…While geographic variation is common in phocid seal calls [7], a detailed study of what appeared to be Northern elephant seal ( Mirounga angustirostris ) dialects turned out to be the result of a population bottleneck and founder effect [51]. The same breeding rookeries recorded nearly 50 years later revealed that the differences found between them in the earlier studies had disappeared, replaced by a much greater call variability between males than found before [52]. Nevertheless, one study on Southern elephant seals ( Mirounga leonina ) provided evidence that males learn at least temporal parameters of their dominance calls from successful conspecifics in wild breeding aggregations [53].…”
Section: Pinnipedsmentioning
confidence: 99%